The Effectiveness and Treatment of Odontogenic Inflammatory Diseases in Frequently ILL Children - S., Tasheva G. (Research Parks Publishing LLC, 2021)
It is known that the diagnosis and treatment of inflammatory diseases of the maxillofacial region are one of the main problems of pediatric dentistry. According to a number of researchers, inflammatory diseases of the maxillofacial region account for up to 21 % of all surgical and 52% of dental diseases in childhood.